2011
DOI: 10.1007/s10096-011-1231-0
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium difficile isolates with increased sporulation: emergence of PCR ribotype 002 in Hong Kong

Abstract: We identified a predominant clone of Clostridium difficile PCR ribotype 002, which was associated with an increased sporulation frequency. In 2009, 3,528 stool samples from 2,440 patients were tested for toxigenic C. difficile in a healthcare region in Hong Kong. A total of 345 toxigenic strains from 307 (13.3%) patients were found. Ribotype 002 was the predominant ribotype, which constituted 35 samples from 29 (9.4%) patients. The mean sporulation frequency of ribotype 002 was 20.2%, which was significantly h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
43
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 56 publications
1
43
2
Order By: Relevance
“…The only survey of ribotypes from Hong Kong was from a single hospital and used a limited number of standard ribotypes for comparison (but did include 017, 046, and 012). Unusually, 70% were of an unknown pattern, with a further 11.6% being nontypeable (16). Only 0.6% of isolates were 017 and 2.3% were 012, with no 046 identified, which is markedly different from our findings in mainland China.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The only survey of ribotypes from Hong Kong was from a single hospital and used a limited number of standard ribotypes for comparison (but did include 017, 046, and 012). Unusually, 70% were of an unknown pattern, with a further 11.6% being nontypeable (16). Only 0.6% of isolates were 017 and 2.3% were 012, with no 046 identified, which is markedly different from our findings in mainland China.…”
Section: Discussioncontrasting
confidence: 99%
“…Only 0.6% of isolates were 017 and 2.3% were 012, with no 046 identified, which is markedly different from our findings in mainland China. However, 10.1% of isolates were 002, representing a local endemic strain which was presumed to be causing cross-infection (16). The distribution of ribotypes in European countries varies quite markedly between countries and is very different from that of mainland China (1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When symptoms developed 4 to 12 weeks after hospital discharge, the association was indeterminate. Infection control nurses would advise frontline health care workers on contact precautions for all diarrheal cases and conduct an outbreak investigation if there was epidemiological evidence of a nosocomial transmission of K. oxytoca, as previously described (11,12). The demographic, clinical, and laboratory findings for patients with health care-associated and community-associated diarrhea with stool cultures that were positive for K. oxytoca were described.…”
Section: Methodsmentioning
confidence: 99%
“…Proactive infection control measures may play a role in preventing nosocomial outbreaks due to norovirus (11), but only a few studies have demonstrated the successful control of nosocomial outbreaks due to C. difficile by a bundle approach (6,27). While the increasing use of broad-spectrum antimicrobials, especially fluoroquinolones, poses a major risk for C. difficile-associated diarrhea and hemorrhagic colitis (22,29), the intrinsic characteristic of hypersporulation of certain ribotypes of C. difficile, such as ribotypes 027 and 002, leading to the prolonged environmental survival of spores, may further contribute to the persistence of nosocomial outbreaks (2,12).…”
mentioning
confidence: 99%